Efficient generation of vesicular stomatitis virus (VSV)-pseudotypes bearing morbilliviral glycoproteins and their use in quantifying virus neutralising antibodies. Issue 6 (3rd February 2016) - Logan, Nicola; McMonagle, Elizabeth; Drew, Angharad A.; Takahashi, Emi; McDonald, Michael; Baron, Michael D.; Gilbert, Martin; Cleaveland, Sarah; Haydon, Daniel T.; Hosie, Margaret J.; Willett, Brian J.
Abstract: Morbillivirus neutralising antibodies are traditionally measured using either plaque reduction neutralisation tests (PRNTs) or live virus microneutralisation tests (micro-NTs). While both test formats provide a reliable assessment of the strength and specificity of the humoral response, they are restricted by the limited number of viral strains that can be studied and often present significant biological safety concerns to the operator. In this study, we describe the adaptation of a replication-defective vesicular stomatitis virus (VSVΔG) based pseudotyping system for the measurement of morbillivirus neutralising antibodies. By expressing the haemagglutinin (H) and fusion (F) proteins of canine distemper virus (CDV) on VSVΔG pseudotypes bearing a luciferase marker gene, neutralising antibody titres could be measured rapidly and with high sensitivity. Further, by exchanging the glycoprotein expression construct, responses against distinct viral strains or species may be measured. Using this technique, we demonstrate cross neutralisation between CDV and peste des petits ruminants virus (PPRV). As an example of the value of the technique, we demonstrate that UK dogs vary in the breadth of immunity induced by CDV vaccination; in some dogs the neutralising response is CDV-specific while, in others, the neutralising response extends to the ruminant morbillivirus PPRV. This technique will facilitate a comprehensive comparison of cross-neutralisation to be conducted across the morbilliviruses.